The Influence of social media on Human and Social Communications: A Sociological Study - Barge Gul Khalili; Tamanna Quraishi; Sahar Fazil (Tinta Emas Publisher, 2024)
The study investigates the impact of social media on human communication and societal dynamics through a survey-based approach involving 200 participants. Through the survey, participants' social media usage patterns, perceptions of its influence on human interaction, self-concept, and societal norms were explored. Additionally, qualitative insights were gathered via semi-structured interviews to enrich understanding. Results revealed diverse viewpoints among participants, with a significant acknowledgment of social media's influence on human interaction and societal norms. The study identified varying degrees of behavioural changes attributed to pervasive social media usage, highlighting implications for individual well-being and societal dynamics. Notably, while a substantial proportion agreed on the platform's positive impact on fostering connections and community engagement, dissenting opinions were also observed, indicating a nuanced perspective. In conclusion, the study underscores the complex interplay between social media usage and human behaviour, emphasizing the need for nuanced approaches in understanding its impact. The findings contribute to a deeper understanding of contemporary communication patterns and societal norms shaped by social media. The study's implications extend to researchers, practitioners, and policymakers, informing strategies for navigating the evolving landscape of digital communication.